ANALYSIS OF FINANCIAL REPORTING AND ACCOUNTABILITY OF THE RAWALELE VILLAGE FOR 2022 FISCAL YEAR - nurul arifin; trisandi eka putri; rosalia agatha bahri; siva nurriani (JABI (Journal of Accounting and Business Issues), 2023)
The village government plays an important role for the progress of the local village, because if the government is not qualified, then the quality of the village will not be as good as desired, for example, for poor facilities and infrastructure, this can be seen from village development, road repairs, and village infrastructure. we can assess easily because the things mentioned earlier can be seen easily from the outside. The village head must report his duties, powers, rights and commitments in managing the village economy. The report is made every quarter, quarter, semester and every year and submitted to the Regent/Mayor. The first semester report consists of a village budget report. Based on the Village Fund in each Regency which has been determined by the central government, the Regent/Mayor has determined the Village Fund in each village. The Village Fund is distributed fairly in each region based on a basic allocation taking into account the number of people, the number of poor people, the area of the village and the difficulty level of the location of each village.